English Teaching Challenges in Remote Areas with Strong Local Languages: An Ethnographic Study - Dwi Husnul Khatima; Sukardi Weda; Muhalim (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This ethnographic study investigates the influence of strong local languages on English language teaching at SMPN 1 Kabangka, Muna Regency, Southeast Sulawesi, using Ethnolinguistic Identity Theory as a framework. Data were collected through classroom observations and semi-structured interviews with three English teachers. The findings reveal that a trilingual shifting strategy—using English, Indonesian, and Muna—is commonly employed to facilitate understanding, although it reduces consistent English exposure and influences students’ pronunciation and accent. Students often lack confidence in using English due to their strong identification with the local language, but this shared background also strengthens teacher-student relationships. Challenges identified through observations and interviews include limited vocabulary, the need for double translation, low student engagement and retention, and minimal exposure to English outside the classroom. Despite these barriers, teachers demonstrate adaptability by integrating local culture, simplifying learning materials, and fostering positive classroom interactions. The study recommends culturally responsive teaching practices, localized curriculum modifications, and targeted professional development to support English language instruction in multilingual and remote educational settings.